Pemanfaatan Limbah Cangkang Telur Untuk Pembuatan Pupuk Organik Cair dan Karya Mozaik Melalui Kegiatan Sosialisasi Dengan Warga Giri Mulyo RT 22, Kelurahan Karang Joang, Balikpapan Utara - Lusi Ernawati; Rizka Ayu Yuniar; Rizka Lestari; Nita Ariestiana Putri (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2023)
Recycled waste management, especially in the Giri Mulyo area, is still less than optimal. Giri Mulyo itself is a community village located in Karang Joang village, North Balikpapan sub-district. Most of the residents of Giri Mulyo work as farmers. Based on information from the surrounding community, there has been a decrease in agricultural yields since the covid-19 pandemic. The decrease in income and the increase in the price of fertilizers sold in the market have forced farmers to reduce the amount of fertilizer applied to their agriculture. Based on these problems, an alternative fertilizer that is more friendly to the pockets of farmers in the Giri Mulyo area is needed. So far, many local people have used food waste to make compost as an alternative to fertilizer. However, this method is considered to take a long time and cause unpleasant odors in their environment and also the durability of compost is still quite low. To overcome these problems, the local community needs to be given socialization about information on making organic fertilizer made from household waste, does not require a long time in the manufacturing process and has a high level of product durability. The basic material used is eggshell waste. Organic fertilizer made from eggshell waste contains a high amount of calcium so that it has a good impact on the maintenance of nutrients in the soil, in line with the increase in plant fertility. In addition to being used as a medium for making liquid organic fertilizer, we also provide training in making mosaic pre-works made from eggshell waste to increase the creativity of local residents. The community service activities began with a location survey and interviews with the partners, Giri Mulyo RT 22 residents and teachers of SDN 012 North Balikpapan, which is located in the same location. Next, socialization on recycling eggshell waste into more valuable products was conducted. The activity ended with the residents involved filling out a questionnaire regarding the community satisfaction survey of the activities carried out. The purpose of this activity is to provide knowledge and insight to the community about making liquid organic fertilizer and mosaic artworks from eggshell waste.